Another step on the road towards standardized outcome reporting for congenital melanocytic naevi: one more to go!. (1st November 2021) - Heppt, M.V.; Steeb, T.; Berking, C.
Abstract: Linked Article:  Fledderus et al. Br J Dermatol 2021; 185:970–977 .